2022
DOI: 10.1038/s41598-022-11178-9
|View full text |Cite
|
Sign up to set email alerts
|

Ambient mass spectrometry for rapid authentication of milk from Alpine or lowland forage

Abstract: Metabolomics approaches, such as direct analysis in real time-high resolution mass spectrometry (DART-HRMS), allow characterising many polar and non-polar compounds useful as authentication biomarkers of dairy chains. By using both a partial least squares discriminant analysis (PLS-DA) and a linear discriminant analysis (LDA), this study aimed to assess the capability of DART-HRMS, coupled with a low-level data fusion, discriminate among milk samples from lowland (silages vs. hay) and Alpine (grazing; APS) sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In this study, the matrix effect did not affect our profiling analysis, as was demonstrated by our CV% values. Note that CV% analysis is routinely used to assess data reproducibility in analytical sciences, and it has also been used in ambient mass spectrometry studies for the same purpose ( Dill et al, 2011 ; Abbassi-Ghadi et al, 2015 ; Bilkey et al, 2016 ; Riuzzi et al, 2021 ; Tata et al, 2022b ). In the present study, we have shown once more that QuEChERS-DART-HRMS is characterized by a CV% lower than 20%, which is in line with United States Food and Drug Administration guidelines for chromatographic analytical techniques ( Guidance, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the matrix effect did not affect our profiling analysis, as was demonstrated by our CV% values. Note that CV% analysis is routinely used to assess data reproducibility in analytical sciences, and it has also been used in ambient mass spectrometry studies for the same purpose ( Dill et al, 2011 ; Abbassi-Ghadi et al, 2015 ; Bilkey et al, 2016 ; Riuzzi et al, 2021 ; Tata et al, 2022b ). In the present study, we have shown once more that QuEChERS-DART-HRMS is characterized by a CV% lower than 20%, which is in line with United States Food and Drug Administration guidelines for chromatographic analytical techniques ( Guidance, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the two datasets were concatenated by low-level data fusion. Low-level data fusion is a simple concatenation of data in a unique table (24,25). The merged dataset was submitted to the LASSO method, a multinomial regression with L1 penalty, with the aims of i) selecting and shrinking of variables, and ii) predicting the health status of animals, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The signals were normalized by sum, whereas each feature was normalized by Pareto scaling. For an initial exploration, the data were concatenated by low-level data fusion [ 21 , 22 , 23 ] (Massaro, 2021, New strategies for the differentiation of fresh and frozen/thawed fish: A rapid and accurate non-targeted method by ambient mass spectrometry and data fusion (part A); Tata, 2022, Ambient mass spectrometry for rapid authentication of milk from Alpine or lowland forage ; Tata, 2022, Detection of soft-refined oils in extra virgin olive oil using data fusion approaches for LC-MS, GC-IMS, and FGC-Enose techniques: The winning synergy of GC-IMS and FGC-Enose ) and submitted to principal component analysis (PCA). Afterwards, the data were split into training (25 samples) and test (8 samples) sets; the training set was used to build the classification model, and the test set was withheld for further validation of the model.…”
Section: Methodsmentioning
confidence: 99%